Azathioprine: its uses in dermatology - Chávez Álvarez, Sonia; Ocampo Candiani, Jorge; Gómez Flores, Minerva; Villarreal Martínez, Alejandra; Herz Ruelas, Maira Elizabeth; Garza Garza, Rubicela (2020)
This is a narrative review of azathioprine. This medication is immunomodulatory and immunosuppressive, and it has been used widely through different medical specialties to modify disease. It has been proven useful for several dermatoses and it has encountered success when used as an off-label indication for other dermatologic diseases. Its mechanism of action is described thoroughly, as well as precautions for monitoring adequate levels in patients using it. Dermatologists should also be aware of the possible adverse events it may present. In dermatology it can be used in bullous and autoimmune diseases, and in other conditions, including intractable pruritus, atopic dermatitis, photodermatoses, psoriasis, and others. Azathioprine offers an alternative as a steroid-sparing agent and this review helps dermatologists prescribe it safely to all patients who require it.